2019
DOI: 10.1002/ece3.5169
|View full text |Cite
|
Sign up to set email alerts
|

The use of cattle Bos taurus for restoring and maintaining holarctic landscapes: Conclusions from a long‐term study (1946–2017) in northern England

Abstract: Cattle Bos taurus can perform valuable ecological functions in the maintenance of high nature value (HNV) pastoral systems. They have also attracted attention as potentially filling the ecological niches of megaherbivores, notably the extinct aurochs Bos primigenius, in rewilding initiatives. Native cattle breeds are recognized under the 1992 Rio Convention as components of biodiversity. They are used in HNV settings, but their conservation as breeds has rarely been an important consideration for their managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Such grazing style suppresses forbs and fails to suppress coarse grasses. Grazing by domestic breeds in more biodiversity-friendly ways is possible (Enri et al 2017;Henning et al 2017, Hall andBunce 2019), but this was not the case in our system. While being demonstrably positive for butter ies associated with poorly competitive forbs, the refaunation did not detectably imperil species associated with coarse grasses or shrubs.…”
Section: Refaunation By Large Ungulatesmentioning
confidence: 76%
“…Such grazing style suppresses forbs and fails to suppress coarse grasses. Grazing by domestic breeds in more biodiversity-friendly ways is possible (Enri et al 2017;Henning et al 2017, Hall andBunce 2019), but this was not the case in our system. While being demonstrably positive for butter ies associated with poorly competitive forbs, the refaunation did not detectably imperil species associated with coarse grasses or shrubs.…”
Section: Refaunation By Large Ungulatesmentioning
confidence: 76%
“…Earlier work had shown that herd fertility is now higher than in the past (calves born per breeding cow year: 1862-18991947-2009Hall & Bunce, 2019) though it is still very low compared with commercial cattle (e.g. Redman, 2016) where a cow would be expected to calve every year.…”
Section: Animalsmentioning
confidence: 97%
“…Such grazing style suppresses forbs and fails to suppress coarse grasses. Grazing by domestic breeds in more biodiversity-friendly ways is possible [32,46,49], but this was not the case in our system.…”
Section: Refaunation By Large Ungulatesmentioning
confidence: 99%
“…Table 1) decreased the explained variation (three Interpreting the CA ordinations by species` attributes gave results consistent across the four variants (Table 2). Species present shortly after the cessation of military use (NT-near threatened, VU-vulnerable, EN-endangered, CR-critically endangered) following [46]. The early 1990s data are from [62], 2009 data from [23], and this study to the 2016-2019 monitoring.…”
Section: Past-present Comparisonmentioning
confidence: 99%